2013
DOI: 10.1161/jaha.113.000329
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Intake, Circulating Vitamin C and Risk of Stroke: A Meta‐Analysis of Prospective Studies

Abstract: BackgroundThough vitamin C supplementation has shown no observed effects on stroke prevention in several clinical trials, uncertainty remains as to whether long‐term, low‐dose intake influences the development of stroke among general populations. Furthermore, the association between circulating vitamin C and the risk of stroke is also unclear. For further clarification of these issues, we conducted a meta‐analysis of prospective studies.Methods and ResultsPubMed and EMBASE databases were searched, and the bibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 50 publications
3
55
1
3
Order By: Relevance
“…Similarly, another meta-analysis of five prospective studies found that each 20 μmol/L of circulating vitamin C was associated with a 19% reduction in stroke risk; however only dietary vitamin C intake, not supplemental intake, had a statistically significant inverse association with stroke risk 28, 29 . This suggests that some micronutrients have stronger associations with reduced stroke risk when obtained from dietary, rather than supplemental sources.…”
Section: Mediterranean Diet and Stroke Preventionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, another meta-analysis of five prospective studies found that each 20 μmol/L of circulating vitamin C was associated with a 19% reduction in stroke risk; however only dietary vitamin C intake, not supplemental intake, had a statistically significant inverse association with stroke risk 28, 29 . This suggests that some micronutrients have stronger associations with reduced stroke risk when obtained from dietary, rather than supplemental sources.…”
Section: Mediterranean Diet and Stroke Preventionmentioning
confidence: 94%
“…Supplements administered at different stages of stroke risk factor development may have different effects 28 . Additionally, the effect of micronutrient supplementation on stroke risk among micronutrient deficient populations has not been well examined in meta-analyses and it is possible that correcting overt micronutrient deficiency would have a differential association with stroke risk compared than what has been observed in populations that are micronutrient replete 28, 29 . Additional studies are needed to further elucidate mechanisms through which micronutrient supplementation may reduce stroke risk in all populations before recommendations on specific micronutrients are warranted.…”
Section: Mediterranean Diet and Stroke Preventionmentioning
confidence: 99%
“…Moreover, p.o. administration of vitamin C (Chen et al ., ) or the effects of combined vitamins C and E, through infusion and capsules (Jaxa‐Chamiec et al ., ; Lee et al ., ; Cook et al ., ), did not demonstrate a major effect of these antioxidant treatments on the clinical outcome of patients. Nevertheless, in diabetic patients, a reduction in 30 day cardiac mortality has been reported (Jaxa‐Chamiec et al ., ).…”
Section: Bench To Bedsidementioning
confidence: 99%
“…The meta-analysis of Chen et al concerned vitamin C intake [48]. Consumption of high doses is preventive in the development of ischemic or hemorrhagic stroke (RR= 0.81; 0.74-0.90).…”
Section: Vitamin Cmentioning
confidence: 99%